2021
DOI: 10.1007/s00520-021-06149-1
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors in patients with advanced cancer and COVID-19: a cohort from the Palliative Care Unit of the Brazilian National Cancer Institute

Abstract: Objective To describe overall survival (OS) in 90 days and to evaluate the prognostic factors in patients with advanced cancer and COVID-19. Methods This is a retrospective cohort study carried out at the Palliative Care Unit of the Brazilian National Cancer Institute. Patients with advanced cancer and COVID-19 confirmed by Reverse Transcription Polymerase Chain Reaction were included. Kaplan-Meier’s curves, log-rank test, and Cox regression were performed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Under the influence of policies related to this period, mortality and infection rates among cancer patients have increased, and interruptions and delays in treatment have caused adverse effects such as poor prognosis and increased psychological stress among patients. The results of a study showed that lung tumour (primary or metastatic), age 60–74 years and chronic obstructive pulmonary disease were independent prognostic factors for palliative care in oncology patients (de Oliveira, da Costa Rosa, et al, 2021). Palliative care setting was a factor of COVID‐19 infection (Fazilat‐Panah et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Under the influence of policies related to this period, mortality and infection rates among cancer patients have increased, and interruptions and delays in treatment have caused adverse effects such as poor prognosis and increased psychological stress among patients. The results of a study showed that lung tumour (primary or metastatic), age 60–74 years and chronic obstructive pulmonary disease were independent prognostic factors for palliative care in oncology patients (de Oliveira, da Costa Rosa, et al, 2021). Palliative care setting was a factor of COVID‐19 infection (Fazilat‐Panah et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…During this period, palliative care patients had longer hospital stays, higher mortality and infection rates, and poorer prognosis. Demand for palliative care is rising among cancer patients, putting them at risk of contracting COVID‐19 (Almeida et al, 2022; de Oliveira, da Costa Rosa, et al, 2021; de Oliveira, Rosa, et al, 2021; Fazilat‐Panah et al, 2022; Jeba, 2020; Moriyama et al, 2021; Onesti et al, 2021; Rahnea‐Nita et al, 2021; Strang et al, 2021; Tashkandi et al, 2021). Palliative care facilities have also been hit by the viral outbreak.…”
Section: Introductionmentioning
confidence: 99%
“…This was expected, considering that KPS and ECOG-PS are recognized as important scales for decision-making in cancer care and have good predictive accuracy for survival. (37)(38)(39)(40) Therefore, even though nutritional risk preceded COVID-19 diagnosis, its predictive accuracy was similar to that of the performance status scales and other prognostic tools, such as the Palliative Prognostic Score (C-statistic: >0.79), the Palliative Prognostic Index (C-statistic: >0.75), (41) the Alternative International Prognostic Score-E (C-statistic: 0.70), (42) and the American Joint Committee on Cancer TNM Classification of Malignant Tumors (C-statistic: 0.74). (43) Published evidence about nutritional risk in patients with cancer and COVID-19 remains scant; however, a strong association has been found between lower survival and nutritional risk among non-cancer patients with COVID-19.…”
Section: ❚ Discussionmentioning
confidence: 99%
“…Therefore, given the increasing cancer burden and prolonged COVID-19 epidemic, identifying prognostic factors of death in patients with cancer affected by COVID-19 could provide timely evidence for high-risk populations. Primary studies conducted on patients with cancer affected by COVID-19 have reported demographic characteristics (such as age7–9), cancer-related characteristics (such as primary cancer site,8 9 lung metastases8 9) and clinical characteristics (such as symptoms,10 11 intensive care units admission,7 10 oxygen therapy,7 10 length of hospital stay,10 comorbidities,9 11 laboratory findings8 11) as prognostic factors of death.…”
Section: Introductionmentioning
confidence: 99%